3D-printable, highly conductive hybrid composites employing chemically-reinforced, complex dimensional fillers and thermoplastic triblock copolymers. Issue 16 (9th February 2017) - Jo, Yejin; Kim, Ju Young; Kim, So-Yun; Seo, Yeong-Hui; Jang, Kwang-Suk; Lee, Su Yeon; Jung, Sungmook; Ryu, Beyong-Hwan; Kim, Hyun-Suk; Park, Jang-Ung; Choi, Youngmin; Jeong, Sunho
Abstract : We demonstrate 3D-printed, highly conductive structures by formulating 3D-printable pastes. Abstract : The use of 3-dimensional (3D) printable conductive materials has gained significant attention for various applications because of their ability to form unconventional geometrical architectures that cannot be realized with traditional 2-dimensional printing techniques. To resolve the major requisites in printed electrodes for practical applications (including high conductivity, 3D printability, excellent adhesion, and low-temperature processability), we have designed a chemically-reinforced multi-dimensional filler system comprising amine-functionalized carbon nanotubes, carboxyl-terminated silver nanoparticles, and Ag flakes, with the incorporation of a thermoplastic polystyrene–polyisoprene–polystyrene (SIS) triblock copolymer. It is demonstrated that both high conductivity, 22 939 S cm −1, and low-temperature processability, below 80 °C, are achievable with the introduction of chemically anchored carbon-to-metal hybrids and suggested that the highly viscous composite fluids employing the characteristic thermoplastic polymer are readily available for the fabrication of various unconventional electrode structures by a simple dispensing technique. The practical applicability of the 3D-printable highly conductive composite paste is confirmed with the successful fabrication of wireless power transmission modules on substrates with extremely uneven surface morphologies.